Corpus callosum size by neurosonography in fetuses with congenital heart defect and relationship with expected pattern of brain oxygen supply. (12th January 2022) - Pérez‐Cruz, M.; Gómez, O.; Gibert, M.; Masoller, N.; Marimon, E.; Lip‐Sosa, D.; Bennasar, M.; Bonet‐Carne, E.; Gómez‐Roig, M. D.; Martínez‐Crespo, J. M.; Gratacós, E.; Eixarch, E.
ABSTRACT: Objective: To evaluate corpus callosum (CC) size by neurosonography (NSG) in fetuses with an isolated major congenital heart defect (CHD) and explore the association of CC size with the expected pattern of in‐utero oxygen supply to the brain. Methods: A total of 56 fetuses with postnatally confirmed isolated major CHD and 56 gestational‐age‐matched controls were included. Fetuses with CHD were stratified into two categories according to the main expected pattern of cerebral arterial oxygen supply: Class A, moderately to severely reduced oxygen supply (left outflow tract obstruction and transposition of the great arteries) and Class B, near normal or mildly impaired oxygenated blood supply to the brain (other CHD). Transvaginal NSG was performed at 32–36 weeks in all fetuses to evaluate CC length, CC total area and areas of CC subdivisions in the midsagittal plane. Results: CHD fetuses had a significantly smaller CC area as compared to controls (7.91 ± 1.30 vs 9.01 ± 1.44 mm 2 ; P < 0.001), which was more pronounced in the most posterior part of the CC. There was a significant linear trend for reduced CC total area across the three clinical groups, with CHD Class‐A cases showing more prominent changes (controls, 9.01 ± 1.44 vs CHD Class B, 8.18 ± 1.21 vs CHD Class A, 7.53 ± 1.33 mm 2 ; P < 0.05). Conclusions: Fetuses with major CHD had a smaller CC compared with controls, and the difference was more marked in the CHD subgroup with expected poorer brain oxygenation. Sonographic CC size could be a clinically feasible marker of abnormal white matter development in CHD. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.